El indigenismo en construcción. Cabildeo interamericano e investigación de campo en los inicios del Instituto Indigenista Interamericano (1940-1946) - López Caballero, Paula (El Colegio de México, A.C., 2021)
Through correspondence, reports and field diaries, this article reconstructs and analyzes the first field work project conducted by the Inter-American Indigenist Institute in the oncocercosis zone of Chiapas and Oaxaca between 1940 and 1946. Through the many financial, scientific and ideological battles that characterized this project, it shows three intersecting processes. First, the slow construction of a perimeter of indigenist “expertise,” in opposition to medical expertise in particular, which became visible at the national and international levels. Second, the plurality of voices, some of them in opposition to each other, that converged within this indigenist perimeter, revealing the undefined state of this field of public intervention. Third, the dispute regarding the definition of the subject to be addressed by indigenism and the nature of its problems.